PROJECT-ORIENTED MANAGEMENT OF ENVIRONMENTAL ENTREPRENEURSHIP IN THE REGIONS - V. V. Sokolenko; D. V. Chabrova; E. L. Koptenok (Вестник университета)
Materials on the development of a modular project for the management and organization of an agricultural cooperative with systematic implementation of tasks and the achievement of commercial and environmental goals have been outlined. The carbon budget of forest ecosystems has been calculated and analyzed, the increase of which is aimed at increasing the yield of “clean” agricultural products with high benefit while reproducing natural systems that affect the improvement of its quality. The methodology and features of the project approach as an instrument for managing the complex economic, environmental and social problems posed by the environmental entrepreneurship of the regions have been analyzed. The economic and environmental performance indicators of the ecopreneur in the production of eco-products in the course of the project have been estimated. The results obtained are intended for associations of agricultural producers, local and regional executive authorities, interested in the development of environmental entrepreneurship and the reproduction of natural ecosystems.